Դիտարկումներ քաղաքական մշակույթի կառուցվածքի վերաբերյալ - Վարդանյան, Լյուդվիգ (YSU Journal of International Affairs, 2018)
Political culture, which reflects the level and essence of political knowledge, orientations, assessments, and actions of people, the content and peculiarities ofspiritual values, events and norms, is considered as one of the main directions of political science research. The essence of a political culture in most cases depends on its structure, which is formed under the influence of certain components determining the value-essence activities of people in the sphere of politics.The article examines different components of the structure of political culture: political experience, political consciousness, political institutions, political behavior and political symbols. An attempt has been made to consider cues as an integral part of political culture, taking into account the fact that anthropological (including ideological) characteristics underlie a person's self-identification and his orientations in politics, and in this sense, political culture can be represented by rational and irrational components.
Keywords: political culture, political system, orientations, political experience, political consciousness, political institutions, political behavior, political symbols